A synthesis technique for radial line slot array antennas with isoflux radiation patterns - Meng, Xiangjun (University of Ottawa (Canada), 2009)
In this thesis the possibility of using radial line slot array (RLSA) antennas to provide low profile isoflux radiation patterns suitable for use as circularly-polarized tracking, telemetry & command (TT&C) antennas on low Earth orbit (LEO) satellites is investigated. The RLSA antenna elements are slot pairs located on concentric circles on the top plate of a radial waveguide. Conventional synthesis techniques cannot be used due to the fact that the RLSA antenna is a non-uniformly spaced array, the elements do not all have the same orientation, and the excitation amplitudes and phases are linked to the actual physical location of a particular slot pair. A technique is therefore developed for synthesizing such an RLSA antenna. Keywords: Antennas, Radial Line Slot Antennas, Isoflux Radiation Patterns
Keywords: Engineering, Electronics and Electrical.